Influence of pregnancy on neuromyelitis optica spectrum disorder. - Kim, W; Kim, S; Nakashima, I; Takai, Y; Fujihara, K; Leite, M; Kitley, J; Palace, J; Santos, E; Coutinho, E; Silva, A; Kim, B; et al. (2012)
OBJECTIVE: To investigate the influence of pregnancy on patients with neuromyelitis optica spectrum disorder (NMOSD). METHODS: A total of 190 women with NMOSD were enrolled from 7 referral hospitals in 4 countries. We reviewed medical records and used a structured questionnaire to investigate gravidity, parity, and the number of relapses during the 2 years before pregnancy, during each trimester of pregnancy, during the first and second trimesters after delivery, and for 6 months thereafter. The annualized relapse rate (ARR) was calculated for each period. RESULTS: Of the 190 women with NMOSD, 40 patients experienced 54 informative pregnancies, and all of them were seropositive for aquaporin-4 antibody. Fourteen patients developed the first symptoms of NMOSD either during the pregnancy (3 patients) or within a year after delivery or abortion (8 and 3 patients, respectively). Twenty-six patients experienced 40 pregnancies after the onset of NMOSD (26 deliveries and 14 abortions [1 spontaneous and 13 elective]). There was one preterm delivery with birth defects and no stillbirths. The ARR during pregnancy did not differ from that before pregnancy, but it increased significantly during the first and second trimesters after delivery (5.3 and 3.7 times, respectively). Moreover, 77% of the deliveries were associated with postpartum relapses. CONCLUSION: The significantly increased relapse rate and numerous cases of NMOSD onset after pregnancy suggest that delivery adversely affects the course of NMOSD. Prospective studies are needed to confirm our findings.